A computer method for design and M-N-ɸ analysis of prestressed RC cross-sections - Chiorean, Cosmin G.; Marchis, Ioana V.; Buru, Marius S. (Journal of Structural Engineering, 2025)
This paper presents a computer method for rapid design and moment-curvature analysis of arbitrary-shaped prestressed reinforced cross-sections that are subjected to biaxial bending and axial force. The method shows very good stability in presence of strain softening effect exhibited by the concrete in compression and tension and convergence stability is not affected by the shape of stress-strain relationships of concrete and the type and amount of reinforcements. The effect of the presstressing strain over inelastic behavior of cross-section has been also investigated. The proposed approach has been found to be very effective to determine the complete moment-curvature relationships showing strength reduction beyond the multiple peak points and reveals that the strain softening effect exhibited by the concrete in compression indicates lower bending capacity of cross section and also “snap-back” behavior. The iterative algorithm, proposed herein, to design the steel reinforcement of prestressed RC cross sections under biaxial bending and axial force, as compared to other iterative methods, is very stable, converging rapidly if the initial value of the required reinforcement area is properly selected. In order to illustrate the proposed approach and its accuracy and efficiency, a computer program has been developed and several computational examples are given to validate the numerical methods developed here.